The magical match - "Baker, E. D" (New York; Bloomsbury, 2017)
"Cory finally comes face-to-face with the fairy guilds that have been threatening to make her give up her matchmaking skills and return to her life as a tooth fairy"-- Provided by the publisher.
Keywords: English Fiction- Fairy-tale